Sea water conversion and salt manufacture - Villanueva, Henry M. Jr.; Koh, Leticia D. (Diliman, Quezon City College of Engineering, 1965)
In this process, sea water, pumped from sea wells, reaches its freezing point during the process and therefore the cooling effect of vaporization causes ice formation in sea water. The ice formed which is now pure water is then melted to give product water. The concentrated brine left off by the product water is further evaporated in crystallizers and sold as crude salt. The product water is ready for home consumption as well as for industrial use. A thorough survey has shown a constant demand for water since the present supply is far beyond coping up with the needs of the consumers. This therefore as well as the reasonably stable cost of product water and crude salt is a boost to the desalination plant. The survey substantiates the economic feasibility of putting up with the plant now. The recommended process together with its design and economics is discussed thoroughly in this report. Total capital investment: 2,798,400 -- Profit before taxes: 770,500 -- % Return on investment: 27.8% -- Pay-out time: 3.6 years.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Saline water conversion; Saline water conversion--Distillation process; Salt industry and trade